2015
DOI: 10.1177/0269215515595274
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of behaviour change interventions to increase physical activity participation in people with multiple sclerosis: a systematic review and meta-analysis

Abstract: Behaviour change interventions provided for relatively short duration (eight to 12 weeks) may increase the amount of physical activity people with multiple sclerosis engage in, but appear to have no effect on the physical components of quality of life and fatigue. Further high quality investigations of the efficacy of behaviour change interventions to increase physical activity participation that focus on dose, long-term impact and method of delivery are warranted for people with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 80 publications
2
61
0
Order By: Relevance
“…A recent review and meta‐analysis of the effectiveness of behaviour change interventions to increase physical activity in persons with MS indicated that behaviour change interventions have a significant effect on physical activity participation (ES = .64), which may result in health benefits. These results indicate that theories of health behaviour change should be incorporated into exercise promotional interventions in MS care.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta‐analysis of the effectiveness of behaviour change interventions to increase physical activity in persons with MS indicated that behaviour change interventions have a significant effect on physical activity participation (ES = .64), which may result in health benefits. These results indicate that theories of health behaviour change should be incorporated into exercise promotional interventions in MS care.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a variety of approaches have been used, for the purposes of this systematic review, behavior change interventions are defined as any psychology-based interventions (used alone or in combination with other interventions, such as exercise therapy) aimed directly or indirectly at behavior change with regard to level of physical activity participation or change in perceived physical function. 23 The National Institute of Health and Clinical Care Excellence (NICE) Public Health Guidance has identified a number of elements for inclusion in an effective behavior change intervention, which includes the use of goal setting, feedback and monitoring, fostering of self-efficacy, and social support. 21 While NICE does not recommended one specific behavior change approach, it does recommend that it should match the service users' needs and be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the intervention was less intensive than other behaviour-change interventions in the literature, 31 it was delivered face-to-face, on a one-to-one basis, unlike previous interventions that delivered group sessions, 32,33 or delivered telephone 20,34 or internet interventions. [17][18][19] Participants emphasised the strong therapeutic relationship was key to developing confidence and competence for PA enactment.…”
Section: Discussionmentioning
confidence: 99%